From Catalytic Hydroborations to Photoluminescent N→Coordinated Boronic Esters - Moždiak, Ondřej; Bíza, Tomáš; Střižík, Lukáš; Růžičková, Zdeňka; Erben, Milan; Dostál, Libor; Hupf, Emanuel; Jambor, Roman (Wiley, 2025)
The N-coordinated Sn(II) cations [{(2,6-iPr2-C6H3)-N = C(Me)-(6-MeO)-C5H3N}SnCl](SnCl3) (1), [{(2,6-iPr2-C6H3)-N = C(Me)-(6-P(O)(OiPr)2)-C5H3N}SnCl](SnCl3) (2), and [{(1,2-(C5H4N-2-CH = N)2CH2CH2)}SnCl](SnCl3) (3) were prepared and used as catalysts in the hydroboration of ketones and aldehydes. Mechanistic and kinetic studies provide evidence that these electrophiles interact with the C & boxH;O bond of the substrates and indicate a pseudo-first-order reaction with a rate constant of k = 70.2 h-1 using 2 mol% of 1. 1 could effectively be used as a catalyst in the hydroboration of a broad range of substrates including, substituted benzaldehydes, heterocyclic carbaldehydes, and aliphatic aldehydes, as well as ketones. Finally, 1 was used in large-scale hydroboration reactions of pyridine-substituted carbaldehydes to prepare the respective pyridine-substituted boronic esters [2-(PinBOCH2)-C5H4N] (4), [2-(PinBOCH2)-4-(MeO)-C5H3N] (5), [2-(PinBOCH2)-6-(MeO)-C5H3N] (6), [2-(PinBOCH2)-6-Br-C5H3N] (7), [2-(PinBOCH2)-5-Br-C5H3N] (8), [3-(PinBOCH2)-C5H4N] (9), and borinate [2-[(BBN)OCH2]-4-(MeO)-C5H3N] (10), which were characterized by NMR spectroscopy, single-crystal X-ray structure analysis, and an analysis of their photoluminescence.
Keywords: cationic complex; hydroboration; photoluminescence; tin